2011
DOI: 10.1051/0004-6361/201016197
|View full text |Cite
|
Sign up to set email alerts
|

Multi-instrument X-ray monitoring of the January 2009 outburst from the recurrent magnetar candidate 1E 1547.0-5408

Abstract: Context. With two consecutive outbursts recorded in four months (October 2008 and January 2009), and a possible third outburst in 2007, 1E 1547.0-5408 is one of the most active transient anomalous X-ray pulsars known so far. Aims. Thanks to extensive X-ray observations, obtained both in the quiescent and active states, 1E 1547.0-5408 represents a very promising laboratory to gain insight into the outburst properties and magnetar emission mechanisms. Methods. We performed a detailed timing and spectral analysis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
50
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 43 publications
9
50
0
Order By: Relevance
“…After submission of our manuscript, we became aware of the work by Bernardini et al (2011) on the 2009 outburst of 1E 1547−5408 using Swift XRT data. A preliminary comparison of their results with ours shows general agreement.…”
Section: Discussionmentioning
confidence: 99%
“…After submission of our manuscript, we became aware of the work by Bernardini et al (2011) on the 2009 outburst of 1E 1547−5408 using Swift XRT data. A preliminary comparison of their results with ours shows general agreement.…”
Section: Discussionmentioning
confidence: 99%
“…They further claim that this behavior is similar to the one observed in AXP 1E2259+586 and not in agreement with an SGR persistent emission. Although the persistent emission energy release cannot be directly measured by GBM or SPI-ACS, Bernardini et al (2011) have shown that for that same time period, it can be at most a factor of five higher in the 13-200 keV than in the 1-10 keV range. The energy released in bursts during a week is thus comparable to the energy released in the persistent emission during an eightmonth period (Scholz & Kaspi 2011), and we conclude that SGR J1550−5418 exhibits similar energetics behavior as other SGR sources .…”
Section: Burst Energeticsmentioning
confidence: 99%
“…In quiescence, luminosities as low as ∼ 10 31 erg s −1 have been observed. The outburst duty cycle of transient AXPs/SGRs is still poorly known: multiple out-bursts have been observed only in SGR 1627−41 and 1E 1547.0−5408 [46,11].…”
Section: Observational Propertiesmentioning
confidence: 99%